Dampak Kebijakan Daendels dan Raffles pada Perubahan Sosial Kontemporer - Khalisha, Khalisha; Nurbaiti, Belkis; Pratama, Rifki Putra (Perkumpulan Program Studi Sejarah Se-Indonesia, 2025)
The policies implemented by Herman Willem Daendels and Thomas Stamford Raffles during the colonial period in the Archipelago had a significant impact on social change. Daendels was known for his infrastructure projects, particularly the construction of the Great Post Road, which accelerated mobility and colonial control but also led to labor exploitation. Meanwhile, Raffles introduced the land rent system, altering land ownership patterns and the agrarian economy, though its implementation faced social challenges. These policies not only influenced the colonial period but also shaped Indonesia’s socio-economic dynamics and governance in the modern era. The administrative reforms introduced by both figures laid the foundation for the bureaucratic system still in use today. This article examines how Daendels’ and Raffles’ policies shaped the social structures of the Archipelago and left a lasting legacy that remains relevant to contemporary Indonesian development policies. Using a historical-critical approach and literature analysis, this study explores the relevance of colonial legacies in Indonesia’s socio-political dynamics while providing a new perspective on the long-term relationship between colonial policies and social transformation.